(NpAM(B'(NQTX SERCQ (B:s (NP(B')QÃ(NSI (B/s)E - (NkORN)QÆJ^UK(B, (No(B. ã.,s)E; (Nw)QÆRINA(B, (Nl(B.,s)E ((NkI)QÇW (B:s)E (NmOLODX(B,s, 1979)
(NdO ZB)QÆRKI WWÆJ[LI WÆDOMÆ P(B'Ã(NSI WIDATNOGO UKRAÇNSXKOGO DRAMATURGA (B- "(NzAGIBELX ESKADRI(B", "(NpLATON kRE^ET(B", "(NbOGDAN hMELXNICXKIJ(B", "(NpAM(B'(NQTX SERCQ(B".s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKA LÆTERATURAs)E